An Educational Process for Requirements Extraction and Use Case Modeling Based on Problem-Based Learning and Knowledge Acquisition - Vasques, Dildre G.; Galindo, Juan F.; dos Santos, Glaucia S.; Gomes, Franciene D.; Garcia-Nunes, Pedro I.; Martins, Paulo S. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2019: Anais do XV Simpósio Brasileiro de Sistemas de Informação, 2019)
The performance of Software Engineering professionals is related, among other factors, to adequate knowledge management practices. Specifically, business vision modeling, requirements, and use-case extraction are central elements in Software Engineering, since they reflect the needs, specificities and functionalities to be considered at the software development stage. All these activities are related to knowledge acquisition and modeling. The goal of this work is to implement an educational process based on knowledge acquisition that assists in more dynamic and active pedagogical practices. This process was tested with software engineering students. The results showed advantages in the adoption of a strategy using principles of knowledge acquisition and modeling. It is possible to conclude that the introduction of the process in the classroom improves students' performance in business vision modeling and in the extraction of use cases and requirements.